Dual-Task Exercise to Improve Cognition and Functional Capacity of Healthy Older Adults - Jardim, Naina Yuki Vieira; Bento-Torres, Natáli Valim Oliver; Costa, Victor Oliveira; Carvalho, Josilayne Patricia Ramos; Pontes, Helen Tatiane Santos; Tomás, Alessandra Mendonça; Sosthenes, Marcia Consentino Kronka; Erickson, Kirk I.; Bento-Torres, João; Diniz, Cristovam Wanderley Picanço (Frontiers in Aging Neuroscience, 2021)
Background It has been suggested that physical inactivity and lack of stimulating cognitive activity are the two most significant modifiable risk factors to impair cognitive function. Although many studies that investigated the cognitive effects of physical exercise and cognitive stimuli in dual-task conditions showed improved cognitive performance, others have not confirmed these findings. The main aim of the present work is to analyze the effects of a dual-task multimodal physical exercise training, at moderate intensity, and cognitive stimulation on cognitive and physical function in healthy older adults. Methods This clinical trial was registered on the Brazilian Registry of Clinical Trials (RBR-9zrx3d). Here we tested the effects of a dual-task multimodal physical exercise training, at moderate intensity, on cognitive and physical function and quality of life in community dwelling older adults. The training protocol included 24 group sessions, 2/week, per 75 min. Cognition was assessed using CANTAB automated neuropsychological tests and Functional Capacity to Exercise tests. Performance was compared from baseline to post intervention and to a non-exercise control group using Mixed Linear Model for repeated measures. Results Control (CG) and dual-task (DTEx) groups progressed differentially over time on performance of episodic memory, sustained visual attention, functional mobility, cardiorespiratory fitness, lower limbs strength resistance, agility, quality of life and dual-task performance with significant improved DTEx performance. Control group did not show any significant changes on these tests except for showing a reduction in dual-task performance. Conclusion We suggest that the dual-task combination of multisensory cognitive stimulation and multimodal moderate physical exercise training, twice a week, may be adopted as an effective program to reduce progression of age-related cognitive decline and improve physical fitness and quality of life on healthy older adults. Clinical Trial Registration Brazilian Registry of Clinical Trials: https://ensaiosclinicos.gov.br/rg/RBR-9zrx3d -UTN code: U1111-1233-6349.